Communication Planning of ICONNET 150678 Contact Center in Handling Customer Complaints - Nadhira Aulyafaza Putra; Asaas Putra (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the communication planning employed by the ICONNET 150678 Contact Center in handling customer complaints through inbound call services based on Philip Lesly's communication planning model. The research method used is in-depth interviews with a qualitative approach involving three internal ICONNET informants. The results show that the ICONNET Contact Center plays a crucial role in managing customer complaints through inbound call services. ICONNET implements systematic steps such as customer data verification, complaint analysis, and the application of First Contact Resolution (FCR). Regular evaluations have led to increased customer satisfaction and a reduction in unresolved complaints. Innovations such as the MyICON+ application facilitate customers in checking bills and reporting issues. Overall, the effective communication strategies and systematic handling of complaints by the ICONNET Contact Center significantly contribute to enhancing customer satisfaction and loyalty.